Ð’Ð»Ð¸ÑÐ½Ð¸Ðµ Ñ€Ð°ÑÑ‚Ð²Ð¾Ñ€Ð¾Ð² ÐºÑ€Ð¸Ð¾Ð¿Ñ€Ð¾Ñ‚ÐµÐºÑ‚Ð¾Ñ€Ð¾Ð² Ð½Ð° Ð²Ñ‹Ð¶Ð¸Ð²Ð°ÐµÐ¼Ð¾ÑÑ‚ÑŒ Ð¸ Ñ‚ÐµÑ€Ð°Ñ‚Ð¾Ð³ÐµÐ½Ð½Ð¾ÑÑ‚ÑŒ ÑÐ¼Ð±Ñ€Ð¸Ð¾Ð½Ð¾Ð² ÐºÐ°Ñ€Ð°ÑÑ (Carassius auratus gibelio Bloch, 1783) - Mikson, Konstantin B.; Revenko, Elena B.; Gapon, Anna A. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2014)
There was studied the effect of cryoprotective solutions, belonging to different classes of chemicals, on the survivaland abnormal development of Prussian carp (Carassius auratus gibelio Bloch, 1783) embryos at the stage of development corresponding to 6 somites. The embryos were incubated during 60 minutes in 10% solutions of cryoprotectants dimethyl sulfoxide (DMSO), 1,2-propane diol (1,2-PD), 1,3-propane diol (1,3 PD), 1,3-butane diol (1,3-DB), 1,4-butane diol (1,4-BD), 1,2-metaoxyethane (1,2-MOE), glycerol, ethylene glycol (EG), methanol, polyethyleneoxide (PEO-1500) and sucrose. Thereafter, the embryos were washed and traced to the stage of development of free-swimming larvae. The highest survival rates for the embryos of Prussian carp (54–67%) was observed in 10% solutions of 1,2-PD, 1,3-PD, EG, PEO-1500, and sucrose, providing the preservation of normally developing embryos close to the control level. Cryoprotective solutions of 1,3-BD, 1,4-BD had higher toxicity: the survival of embryos in those made 40–49%. In the solutions of 1,2-MOE, DMSO, glycerol and methanol cryoprotective agents the survival rate of embryos was minimal. The highest level of teratogenic embryos was observed after incubation in the cryoprotectant solutions of 1,2-MOE and methanol.Probl Cryobiol Cryomed 2014; 24(2):149-156.